ANALISIS KESALAHAN DALAM PENGGUNAAN SIMPLE PAST TENSE OLEH SISWA SMA NEGERI 2 MANADO - HARJONO, KRISTANTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research, entitled â€œError Analysis in The Use of Past Tense by Students of SMA Negeri 2 Manado,â€ is an attempt to identify, classify and analyze the kinds of errors in the use of past tense by students in Senior High School. This research is expected to give a contribution for the readers, in terms of understanding about the error analysis especially in the use of simple past tense. The method used in this research is descriptive method. Ellisâ€™s theory is used to explain how to analyze the use of past tense by students in SMA Negeri 2 Manado. Data was taken from 48 students in XI MIA 2 and XI MIA 4 of SMA Negeri 2 by teaching and giving them several tests (fill in the blank, true or false and essay) containing simple past tense material. The result of this research shows that there are three kinds of errors made by students; there are omission, misinformation and misordering. Errors of omission made by students are omission verb ending (-ed, -d), did, not, regular and irregular verb, and to be. Errors of misinformation are regular and irregular verb, past form of irregular verb, to be, and to do. Errors of misordering are verb and object, subject, and time compliment. Key word : simple past tense, error analysis, omission, misinformation and misordering. Â